2003
DOI: 10.1074/jbc.m204891200
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilation by the Calcium-mobilizing Messenger Cyclic ADP-ribose

Abstract: In artery smooth muscle, adenylyl cyclase-coupled receptors such as ␤-adrenoceptors evoke Ca 2؉ signals, which open Ca 2؉ -activated potassium (BK Ca ) channels in the plasma membrane. Thus, blood pressure may be lowered, in part, through vasodilation due to membrane hyperpolarization. The Ca 2؉ signal is evoked via ryanodine receptors (RyRs) in sarcoplasmic reticulum proximal to the plasma membrane. We show here that cyclic adenosine diphosphate-ribose (cADPR), by activating RyRs, mediates, in part, hyperpol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 50 publications
(37 reference statements)
6
60
2
Order By: Relevance
“…3,4,7 In plants, studies of Ca 2C release in Arabidopsis identified AtTPC1 as a channel 8 that mediates the slow vacuolar current, 9 regulating germination and stomatal movement. 10 TPCs have been shown to regulate differentiation, 11 smooth muscle contraction 12 and endothelial cell activation, 13 consistent with previous studies implicating nicotinic acid adenine dinucleotide phosphate (NAADP)-induced Ca 2C release in these events, [14][15][16] and supported by several overexpression, knockdown and knockout models. 3,4,6,17 Regulation and affinity of TPC ion channels is a contentious issue.…”
Section: Introductionsupporting
confidence: 65%
“…3,4,7 In plants, studies of Ca 2C release in Arabidopsis identified AtTPC1 as a channel 8 that mediates the slow vacuolar current, 9 regulating germination and stomatal movement. 10 TPCs have been shown to regulate differentiation, 11 smooth muscle contraction 12 and endothelial cell activation, 13 consistent with previous studies implicating nicotinic acid adenine dinucleotide phosphate (NAADP)-induced Ca 2C release in these events, [14][15][16] and supported by several overexpression, knockdown and knockout models. 3,4,6,17 Regulation and affinity of TPC ion channels is a contentious issue.…”
Section: Introductionsupporting
confidence: 65%
“…Intracellular cADPR concentrations are known to be regulated in many different ways: in one such mechanism, ADP-ribosyl cyclase or CD38 seems to be coupled directly with neurotransmitter or hormone receptors such as muscarinic acetylcholine or metabotropic glutamate receptors via different G proteins on the membrane surface (Higashida et al, 1997(Higashida et al, , 1999(Higashida et al, , 2007; or phosphorylation downstream of the G-protein-coupled receptor signaling pathway (Boittin et al, 2003;Sternfeld et al, 2003). Specifically, the activation of ADP-ribosyl cyclase or CD38 by cyclic GMP-or cyclic AMP-dependent protein kinases has been reported in Aplysia californica (Graeff et al, 1998), LAK cells (Rah et al, 2005) and artery smooth muscle cells (Boittin et al, 2003). However, there have been no previous reports regarding the mechanisms by which ADP-ribosyl cyclase and CD38 are activated after OT receptor stimulation in the hypothalamus, leading to secretion of OT.…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence indicates that cADPR synthesis by ADP-ribosyl cyclases is stimulated through cell-surface heterotrimeric G-protein-coupled receptor signaling. The receptors involved in ADP-ribosyl cyclase activation include the ␤-adrenergic (11,12), angiotensin II (13), and muscarinic (14) receptors. Activation of ADP-ribosyl cyclase/CD38 by cGMP has been reported (15,16), and cAMP-dependent activation of the enzyme has also been observed in artery smooth muscle cells (12) and cardiomyocytes (17).…”
mentioning
confidence: 99%
“…The receptors involved in ADP-ribosyl cyclase activation include the ␤-adrenergic (11,12), angiotensin II (13), and muscarinic (14) receptors. Activation of ADP-ribosyl cyclase/CD38 by cGMP has been reported (15,16), and cAMP-dependent activation of the enzyme has also been observed in artery smooth muscle cells (12) and cardiomyocytes (17). However, the molecular mechanism of ADPribosyl cyclase/CD38 activation has not been completely elucidated.…”
mentioning
confidence: 99%